Karakteristik Total Padatan Tersuspensi (Total Suspended Solid) Dan Kekeruhan (Turbidity) Secara Vertikal Di Perairan Teluk Benoa, Bali - Hendrawan, I Gede; Ulinuha, Devi; Maharta, I Putu Ranu Fajar (Journal of Marine and Aquatic Sciences; Vol 2 No 1 (2016)DO - 10.24843/jmas.2016.v2.i01.29-33, 2016)
Benoa bay is one of estuary that located in the Southern part of Bali Island, and as a strategic tourism destination. The increased of the human activity has an important role to give an ecological pressure for the seawater ecosystem in the Benoa bay. Total suspended solid (TSS) and turbidity is one of the important indicators that could be determining the quality of the seawater. As the estuary, Benoa bay received fresh water from the river discharge that also potentially carries any material to the bay. In addition, port activity is also has an important role in contributing a various material to the Benoa bay. From this research, we found that the TSS concentration and the turbidity are higher in the surface water and also in the bottom layer. TSS concentration and the turbidity also varied from the bay mouth trough the line of vessel onto the inner of bay. TSS concentration and turbidity in the bay mouth has a smaller concentration rather than in the inner part of bay. TSS concentration and turbidity in the inner of bay could be caused by the port activity. In addition, seawater circulation is also has an importan factor to contributing the TSS concentration and the turbidity. Sea current would be erroted the seabottom and with the different shape of the topography could be increased the TSS and turbidity.
Keywords: TSS, Tubidity, Benoa, estuary